Solution Structure of the N-Terminal Domain of Mediator Subunit MED26 and Molecular Characterization of Its Interaction with EAF1 and TAF7. Issue 20 (13th October 2017) - Lens, Zoé; Cantrelle, François-Xavier; Peruzzini, Riccardo; Hanoulle, Xavier; Dewitte, Frédérique; Ferreira, Elisabeth; Baert, Jean-Luc; Monté, Didier; Aumercier, Marc; Villeret, Vincent; Verger, Alexis; Landrieu, Isabelle
Abstract: MED26 is a subunit of Mediator, a large complex central to the regulation of gene transcription by RNA Polymerase II. MED26 plays a role in the switch between the initiation and elongation phases of RNA Polymerase II-mediated transcription process. Regulation of these steps requires successive binding of MED26 N-terminal domain (NTD) to TATA-binding protein-associated factor 7 (TAF7) and Eleven-nineteen lysine-rich in leukemia-Associated Factor 1 (EAF1). In order to investigate the mechanism of regulation by MED26, MED26-NTD structure was solved by NMR, revealing a 4-helix bundle. EAF1 (239–268) and TAF7 (205–235) peptide interactions were both mapped to the same groove formed by H3 and H4 helices of MED26-NTD. Both interactions are characterized by dissociation constants in the 10-μM range. Further experiments revealed a folding-upon-binding mechanism that leads to the formation of EAF1 (N247–S260) and TAF7 (L214–S227) helices. Chemical shift perturbations and nuclear Overhauser enhancement contacts support the involvement of residues I222/F223 in anchoring TAF7 helix to a hydrophobic pocket of MED26-NTD, including residues L48, W80 and I84. In addition, Ala mutations of charged residues located in the C-terminal disordered part of TAF7 and EAF1 peptides affected the binding, with a loss of affinity characterized by a 10-time increase of dissociation constants. A structural model of MED26-NTD/TAF7 complex shows bi-partite components, combining ordered and disordered segments, as well as hydrophobic and electrostatic contributions to the binding. This study provides molecular detail that will help to decipher the mechanistic basis for the initiation to elongation switch-function mediated by MED26-NTD. Graphical abstract: Highlights: MED26 mediates a switch between transcription phases by interacting with TAF7 and EAF1. A folding-upon-binding mechanism of TAF7 and EAF1 interacting peptides is observed. The interaction mapped to a groove between helices H3 and H4 of MED26-NTD. TAF7 interaction is bi-partite, involving distinct hydrophobic and charged clusters. This study reveals molecular detail of MED26 function in transcription regulation.